Analysis of the excitation function of deuteron induced nuclear reaction on Neon-20 using COMPLET code - Guadie Degu Belete; Yihunie Hibstie Asres; Senamaw Mequanent Zegeye; Yesigat Enawugaw Alemu (Nuclear Energy and Technology, 2024)
In this study deuteron induced nuclear reaction on 20Ne target was studied to get nuclear information about 18F and 21Na radioisotopes which are widely used in medical and nuclear reactor technologies respectively. This nuclear reaction is important to get nuclear data since the produced radioisotope is widely used in nuclear medicine due to its appropriate short half-life and positron emitter. The main objective of the study was to analyse and interpret the behaviour of the resulting reaction cross section. It also aimed to compare the computed theoretical result with the experimental data retrieved from IAEA EXFOR for its validity. From such nuclear reaction, the reaction cross sections of 20Ne(d, α)18F, 20Ne(d, x)18F, and 20Ne(d, n)21Na reaction channels were computed using a nuclear computational code called COMPLET. The computed reaction cross sections for each channel were found in good agreement with the experimental data within the specified energy range and show a strong correlation as assessed by Pearson’s correlation coefficient. The analysis of the result shows that compound nucleus reaction is found the dominant reaction mechanism at the lower energies of the projectile.